PENGARUH SENAM LANSIA TERHADAP PENURUNAN GULA DARAH SEWAKTU PADA LANSIA DIABETES MELITUS DI DESA PATRASANA KABUPATEN TANGERANG - Euis Sartika; Inna Solihati Embrik; Zahrah Maulidia Septimar (Yayasan Nusantara Hasana Berdikari, 2023)
Elderly is someone who is over 60 years old. In the elderly there is an aging process which is a physiological process. The increase in blood sugar levels that are commonly experienced by the elderly due to the aging process can be prevented by exercising regularly. Elderly gymnastics is a light exercise that is easy to do and can be applied to the elderly. Research objective to determine the effect of elderly exercise on blood sugar levels in the elderly with diabetes mellitus. Research Methods: This study uses a quantitative method with a pre-post test. This study uses the Paired Samples T-Test which is used to determine the effect of elderly exercise on decreasing blood sugar levels before and after elderly exercise. The results of this study showed that the average value of GDS before the elderly exercise was 258.10 while after the elderly exercise was carried out it was 253.30 with an average decrease of 4.8. There is no effect of elderly exercise on blood sugar levels in the form of increasing blood sugar levels in the elderly.